Pengaruh Strategi Diversifikasi, Efisiensi Operasional dan Keputusan Pendanaan terhadap Nilai Perusahaan - Selya Nuraini; Niswah Baroroh (Vokasi : Jurnal Riset Akuntansi, 2026)
This study aims to analyze the effect of diversification strategy, operational efficiency, and financing decisions on firm value, with Corporate Social Responsibility (CSR) as a moderating variable. This study employs a quantitative approach using secondary data from companies in the consumer non-cyclical sector during the 2022–2024 period. The research sample was determined using a purposive sampling technique, resulting in 212 units of analysis in the form of unbalanced sampling. The data analysis techniques used were panel data regression and Moderated Regression Analysis (MRA). The findings of this study indicate that financing decisions have a significant positive effect on firm value, while diversification strategy and operational efficiency do not have a significant effect on firm value. CSR is proven to weaken the effect of financing decisions on firm value. However, CSR is not proven to moderate the effect of diversification strategy and operational efficiency on firm value